2009
DOI: 10.1093/annhyg/mep050
|View full text |Cite
|
Sign up to set email alerts
|

Guidance Values for Surface Monitoring of Antineoplastic Drugs in German Pharmacies

Abstract: The introduction of TGVs helps to reduce occupational exposure and allows pharmacy personnel to benchmark their own contamination levels. This provides a basis for improvement in occupational safety precautions and for regular contamination controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…However, as no occupational exposure limits have been established, we recommend that North American researchers and/or occupational hygienists consider developing suitable hygienic guidance values based on surface contamination levels that have been recently obtained from Canadian and American healthcare facilities. Such hygienic guidance values have previously been proposed in two European countries—one for Germany [63] and another set of values for Sweden [39] . Given the potential difference in practices and training regimens, the hygienic guidance values developed in Europe may not be practical or suitable to North American facilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, as no occupational exposure limits have been established, we recommend that North American researchers and/or occupational hygienists consider developing suitable hygienic guidance values based on surface contamination levels that have been recently obtained from Canadian and American healthcare facilities. Such hygienic guidance values have previously been proposed in two European countries—one for Germany [63] and another set of values for Sweden [39] . Given the potential difference in practices and training regimens, the hygienic guidance values developed in Europe may not be practical or suitable to North American facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The high number of positive biological samples found by Yoshida et al [11] demonstrates the need to adopt more sensitive analytical techniques; the FBAL determination method proposed by the Japanese research group, a modification of that proposed by Rubino et al [33], using gas chromatography coupled with high-resolution MS, allowed for a lower order of magnitude of sensitivity than other methodologies. No critical issues with Pt were noticed by us; Schierl et al [10] found that nearly all Pt samples were above the detection limit (0.025 pg/cm 2 ). The significant reduction in surface contamination from ADs found in 2009-2017 in Careggi University Hospital is attributable to: ■ training and re-training of the staff, ■ the use of closed systems to prevent any escape of hazardous drugs, ■ the development of a new cleaning technique for floors and work surfaces.…”
Section: Discussionmentioning
confidence: 83%
“…That list was recently updated in 2016 to include drugs newly approved by the U.S. Food and Drug Administration (FDA) [9]; slightly more than a half of these hazardous drugs are classified as antineoplastic/cytotoxic agents. Despite the NIOSH guidelines, studies continue to document ongoing exposure to antineoplastic drugs (ADs), in part because compliance has been voluntary and irregular, and in part since contamination is not being regularly monitored at the ward level [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States Occupational Safety and Health Administration has set threshold limit values for platinum salts in workplace air. 22) Some studies have centered on workplace contamination and occupational exposure to anticancer drugs. [3][4][5][6][7] Occupational exposure to an anticancer drug is affected by its chemical properties such as volatility, molecular weight, and liposolubility.…”
Section: Discussionmentioning
confidence: 99%